مقارنة الموجودات التنظيرية لعنق الرحم مع لطاخة بابانيكولاو - سلمان صفاء; النقري محمد; ططري إياد (Latakia University Journal -Medical Sciences Series, 2019)
تم إجراء البحث في قسم التوليد وأمراض النساء بمشفى الأسد الجامعي في اللاذقية في الفترة ما بين 4\8\2005 و4\8\2007 ، حيث شملت الدراسة 300 مريضة مسحت للتحري عن الآفات التنشؤية والسرطانية في عنق الرحم، باستخدام لطاخة بابانيكولاو والتنظير المكبر لعنق الرحم, وقيمت نتائج كل اختبار على حدة, ومن ثم العلاقة بين نتائج التنظير واللطاخة واعتبار الفحص النسيجي كمعيار تشخيصي أكيد لتحديد الحساسية والنوعية لكل من الاختبارين. وكانت حساسية التنظير أعلى من حساسية اللطاخة في حين نوعية التنظير أقل من نوعية اللطاخة وعند إشراك لطاخة بابانيكولاو مع تنظير عنق الرحم المكبر ارتفعت الحساسية إلى 92 % . ومن ثم دراسة العلاقة بين نتائج التنظير المكبر لعنق الرحم ولطاخة بابانيكولاو مع بعض عوامل الخطورة لسرطان عنق الرحم حيث وجدنا ارتفاع في نسبة وجود البشرة الشاذة في عنق الرحم في الحالات الآتية: العمر المتقدم ، التدخين ، الحمول المتعددة, فترة الزواج, الزواج في سن مبكرة . The study was carried in the Department of Obstetrics and Gynecology at Al-Assad University Hospital in Lattakia between 4/8/2005 & 4/8/2007. The study included 300 patients who were screened for cervical intraepithelial neoplasia and invasive cervical cancer by simultaneous papanicolaou smear and colposcopy. The accuracy of each screening test was evaluated independently, and the results of colposcopy and papanicolaou smear were compared with the histological results like the "gold standard" to detect the sensitivity and specificity of both screening tests. Colposcopy was more sensitive than the papanicolaou smear; whereas its specificity was less than papanicolaou smear. When we combined the papanicolaou smear and colposcopy, the sensitivity increased to( 92) % . We also studied the relation of papanicolaou smear and colposcopy with the risk factors of cervical cancer. There was an increase in the incidence of epithelial abnormalities of the cervix in the following cases: age, cigarette smoking, multiple pregnancy, period of marriage, and early marriage.